The prognostic value of neutrophil-to-lymphocyte ratio in adult carbapenem-resistant Klebsiella pneumoniae infection: a retrospective cohort study - Wang, Zhongjie; Li, Renhua; Yuan, Zhe; Zhang, Zuli; Qian, Keli (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundSystemic inflammatory indicators such as neutrophil-to-lymphocyte ratio (NLR) can effectively predict the prognosis of various inflammatory diseases. However, its prognostic effect on patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) infection is little known. The objective of this study was to investigate the risk factors for mortality associated with CRKP infection and the clinical value of NLR in predicting prognosis in these patients.MethodsA total of 190 inpatients with CRKP infection from 1 January 2023 to 31 December 2023 were enrolled in this study, namely, 73 fatal cases and 117 survival cases in hospital. The medical data and examination results of these patients were collected. A logistic regression analysis was performed to assess the association between the NLR on the day of CRKP infection onset and all-cause mortality in hospital.ResultsThe overall mortality rate of patients with CRKP infection was 38.42% (73/190). Of the 190 patients, 91 were co-infected with carbapenem-resistant Acinetobacter baumannii/carbapenem-resistant Pseudomonas aeruginosa (CRAB/CRPA). Multifactor regression analysis confirmed that carbapenem exposure in the past 14 days, central line insertion, and chronic Foley catheter requirement were independent risk factors for carbapenem-resistant bacteria co-infection. The multivariate analysis shows that admission to an ICU, co-infection with CRAB/CRPA, and higher NLR were independent risk factors for the mortality in hospital, while appropriate treatment within 3 days was an independent protective factor. The area under the curve (AUC) of the NLR was 0.696, and the cutoff value of the NLR was 10.73.ConclusionsThe NLR on the day of CRKP infection onset, admission to an ICU, and co-infection with CRAB/CRPA were identified as independent risk factors for all-cause mortality of patients with CRKP infection, while appropriate treatment within 3 days was recognized as an independent protective factor. The NLR serves as a conveniently accessible and independent prognostic biomarker for patients with CRKP infection.